Influence of key geometric parameters on the aerodynamic performance of a supersonic compressor cascade. (September 2018) - Cui, Cui; Zhou, Zhenggui; Zhang, Jinhuan; Tao, Sheng
The shocks in a supersonic/transonic axial compressor can increase the pressure ratio and cause flow losses. Therefore, it is essential to organize the shock wave pattern in the flow passage to reduce these losses. This study uses a numerical simulation method to study the influences of the leading-edge radius, cascade solidity, and pre-compression on the aerodynamic performance of a supersonic cascade. The cascade is designed using the pre-compression method to reduce shock losses; the inlet Mach number is 2.0 and the total pressure ratio is approximately 3.4. The results indicate that the cascade efficiency and stall margin decrease with an increase in the leading-edge radius; however, when the leading-edge radius is less than 0.1 mm, the influences of its change decrease. As cascade solidity increases, the stall margin first increases and then decreases. The larger the degree of pre-compression, the smaller the Mach number in front of the first oblique passage shock and the higher the efficiency; however, a large pre-compression effect can cause the ending normal shock to move upstream, decreasing the stall margin.